Q-Apostol-Bernoulli polynomials and q-power sums - Luo, Qiu-Ming (Utilitas Mathematica, 2014)
We show the basic properties and generating functions of the q-Apostol-Bernoulli polynomials. Some recursive formulas are derived in series of the q-power sums. We also provide a explicit relation between the q-Apostol-Bernoulli polynomials and q-Hurwitz-Lerch zeta function.